Tinjauan Literatur tentang Etika Bisnis Syariah Berdasarkan Prinsip Amanah dan Adil - Abdul Haqi; Madian Muhammad Muchlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines sharia business ethics with a focus on the principles of amanah and justice through a literature review approach. This article aims to understand the role of both principles in building business ethics that are in accordance with sharia values. The results of the study indicate that amanah and justice are not only moral foundations, but also important pillars in sharia business practices, both theoretically and applicatively. This study provides in-depth insight into the relevance of these principles in facing contemporary business challenges.